ChemInform Abstract: A Phosphine‐Mediated Stereocontrolled Synthesis of Z‐Enediynes by a Vicinal Dialkynylation of Ethynylphosphonium Salts. Issue 2 (January 2015) - Reichl, Kyle D.; Radosevich, Alexander T.
Abstract A convenient method is elaborated for the two‐step preparation of Z‐enediynes (VI) via a dialkynylation of isolated ethynylphosphonium bromides (III).